Job Rotation Practices and Employees Performance: Do Job Satisfaction and Organizational Commitment Matter? - Abdul-Razak Suleman; Bernard Bekuni Boawei Bingab; Kwame Owusu Boakye; Richard Sam-Mensah (SEISENSE Business Review)
Purpose: This study sought to propose and test a model that examines the mediating roles of job satisfaction and organizational commitment in the nexus between job rotation practices and employee performance.